Since you're only interested in x, you can use the first equation to write an expression for y that can be substituted into the second equation.
.. y = k -x
.. 2x +3(k -x) = k +1
.. -x +3k = k +1 . . . . . collect terms
.. 2k -1 -x = 0 . . . . . . subtract k+1
.. 2k -1 = x . . . . . . . . .add x
The 3rd selection is appropriate.
For ever input, there is one ouput
it means we can't repeat the same x with a different y
but repeats of y's are allowed
pick any numbers that haven't been used as an input
-5 isn't taken
0 is taken
11 is taken
-1 is taken
2 is not taken
17 is taken
so -5 and -1 or A and D are the answers
This is the answer if you mean 719-26
700-30= 670
The answer is -1 7/8 in lowest terms.
Answer:
377.9
Step-by-step explanation:
368.8 + 9.1 = 377.9